2018
DOI: 10.1136/bmjopen-2017-019387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the feasibility and performance of early warning scores to identify patients at risk of adverse outcomes in a low-middle income country setting

Abstract: ObjectiveThis study describes the availability of core parameters for Early Warning Scores (EWS), evaluates the ability of selected EWS to identify patients at risk of death or other adverse outcome and describes the burden of triggering that front-line staff would experience if implemented.DesignLongitudinal observational cohort study.SettingDistrict General Hospital Monaragala.ParticipantsAll adult (age >17 years) admitted patients.Main outcome measuresExisting physiological parameters, adverse outcomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
(34 reference statements)
0
30
0
Order By: Relevance
“…We conducted a secondary analysis of 9 data sets: 8 cohort studies (5 prospective and 3 retrospective) and 1 randomized clinical trial. [8][9][10][11][12][13][14][15] Of the countries represented in this study (Bangladesh, Haiti, India, Indonesia, Myanmar, Rwanda, Sierra Leone, Sri Lanka, Thailand, and Vietnam), 3 are classified as low income, 6 as lower middle income, and 1 as upper middle income by the World Bank. 16 Patients were recruited to the cohorts from a range of hospital settings, including small community hospitals, military hospitals, rural regional hospitals, national referral hospitals, and specialty infectious disease hospitals.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
“…We conducted a secondary analysis of 9 data sets: 8 cohort studies (5 prospective and 3 retrospective) and 1 randomized clinical trial. [8][9][10][11][12][13][14][15] Of the countries represented in this study (Bangladesh, Haiti, India, Indonesia, Myanmar, Rwanda, Sierra Leone, Sri Lanka, Thailand, and Vietnam), 3 are classified as low income, 6 as lower middle income, and 1 as upper middle income by the World Bank. 16 Patients were recruited to the cohorts from a range of hospital settings, including small community hospitals, military hospitals, rural regional hospitals, national referral hospitals, and specialty infectious disease hospitals.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
“…The few studies performed in low-and middle-income countries have shown a wide variation in the performance of EWS. 1,17,18 In addition to patient population, the performance of any EWS must also depend on the accuracy of the vital sign recordings used to calculate it. In many studies complete sets of vital signs were often not performed, and/or could not be measured because the equipment required was not available.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies complete sets of vital signs were often not performed, and/or could not be measured because the equipment required was not available. [17][18][19] In this study a considerable amount of care with vital sign measurement was taken. The READS computer system has been used at Kitovu to collect vital signs at the bedside since 2016, and for this study an electrocardiograph was used to assess heart rate, a computer application to accurately determine respiratory rate measured over 60 seconds, and a well-validated blood pressure machine to record blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The platform has assisted clinicians in the care of over 100 000 patient episodes, from critical care admission, through to outcomes at 30 days following discharge 24. The digital intensive care unit (ICU) platform has increased availability of variables for benchmarking acuity of admissions and supported the validation of prognostic models 11 19 20 25. The platform has also facilitated participation in international multisite observational studies on ventilation management 26.…”
Section: Discussionmentioning
confidence: 99%
“…While there is much in the literature to recommend what data should be collected,7 10 11 there is limited practical advice or examples on how day-to-day clinical information can be successfully captured, especially in overstretched and under-resourced LMIC settings 1. It is noticeable in HIC settings that healthcare providers and researchers have increasingly turned towards technology and digital surveillance in order to achieve the breadth and saturation of continuous information needed to improve care.…”
Section: Introductionmentioning
confidence: 99%